Structural design code data handbook - De Gracia, Engracio P. (General planning & engineering series, 2003)
This is a reference material covering the different structural materials and systems. It is intended for practicing structural designers who need easy access to essential information on materials, structural loads, design tables, basic theories and standard practices. It also highlights professional applications.